2022
DOI: 10.3389/fpls.2022.944308
|View full text |Cite
|
Sign up to set email alerts
|

Post-flowering Soil Waterlogging Curtails Grain Yield Formation by Restricting Assimilates Supplies to Developing Grains

Abstract: Soil waterlogging is among the major factors limiting the grain yield of winter wheat crops in many parts of the world, including the middle and lower reaches of the Yangtze River China. In a field study, we investigated the relationship between leaf physiology and grain development under a varying duration of post-flowering waterlogging. A winter wheat cultivar Ningmai 13 was exposed to soil waterlogging for 0 (W0), 3 (W3), 6 (W6), and 9 d (W9) at anthesis. Increasing waterlogging duration significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The effects of these patterns of drought (timing and severity) explain well the significantly higher mean TKW value obtained in 2021 than those in 2017. The considerably lower mean TKW recorded in 2014 is consistent with research showing that prolonged soil wetness after anthesis restricts the amount of assimilates available to growing grains, hence diminishing the development of grain yield [45]. The observed variance in the protein content in the collection under study may potentially be explained by the precipitation oscillations among the three crop seasons.…”
Section: Phenotypic Variationsupporting
confidence: 84%
“…The effects of these patterns of drought (timing and severity) explain well the significantly higher mean TKW value obtained in 2021 than those in 2017. The considerably lower mean TKW recorded in 2014 is consistent with research showing that prolonged soil wetness after anthesis restricts the amount of assimilates available to growing grains, hence diminishing the development of grain yield [45]. The observed variance in the protein content in the collection under study may potentially be explained by the precipitation oscillations among the three crop seasons.…”
Section: Phenotypic Variationsupporting
confidence: 84%
“…However, in this study, the photosynthetic performance did not fully recover on the 16th day for all water treatments and cultivars compared to the 8th day (Figures 2, 3, S1). This incomplete recovery of photosynthetic potential might be caused by leaf senescence after flowering, especially for the waterlogged wheat plants (Hossain et al, 2011; Ma et al, 2022b). In addition, cultivar YM15 showed a smaller decrease in photosynthetic performance on the 8th day after flowering, 1000‐kernel weight and yield in the WL treatment compared to cultivar YM24 when compared with their respective CK treatments (Figures 2A, S1A; Tables 2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the actual photochemical efficiency (Φ PSII ) of photosystem II in wheat plants compared to conventional water management has been observed during waterlogging (Ma et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin also triggers ethylene production and alleviates growth inhibition induced by WS in Alfalfa plants (Zhang et al, 2019). In summary, plant hormones play crucial roles in seed development and previous studies have reported that WS leads to the upregulation of genes such as ACO, ACS , and TDC in plants (Ma, Hou, et al, 2022; Nguyen et al, 2018) that promotes an increase in melatonin or ethylene content to enhance WS tolerance. However, research has found that under WS, the starch synthases SUS and AGPase are inhibited by increasing ethylene content in the wheat endosperm and restricted kernel development (Kuanar et al, 2019).…”
Section: Introductionmentioning
confidence: 92%